Communication of Critical Consciousness in Peasant Movement - Wijanarko, Wijanarko; Sarwoprasodjo, Sarwititi; Rangkuti, Parlaungan Adil (Makara Human Behavior Studies in Asia, 2014)
Development discourse at grassroots level gave birth to farmers’movement as a counterhegemonic response to the dominant state development. Critical awareness of communication processes plays a major role in sensitizing the farmers on forms of oppression and transforming them into a practical movement. The use of the concept of consciousness raising in the form of channels of communication, forms of communication, and various techniques of awareness can affect awareness, motivation and identity transformation of the participants. This article aims to understand the communication processes generating awareness of the peasant movement in addressing growing issues and their relationships with participation in a collective action. Method of research used is qualitative approach with the case subjects involving 4 groups of farmers SPPQT basis (Serikat Paguyuban Petani Qaryah Thayyibah). The results show that participation in collective action is influenced by the communication process of critical awareness generated by SPPQT through the use of various communication channels both at base level and at the level of public. Critical awareness of communication carried out by SPPQT spawned a variety of critical awareness of participants because participants make different meanings of reality, and instrumental motivation is always inherent in any collective action.